2000
DOI: 10.1007/s007740050103
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gene expression associated with BMP-2-induced osteoblast and adipocyte differentiation of mesenchymal progenitor cell 3T3-F442A

Abstract: The pluripotent mesenchymal stem cells give rise to osteoblasts, adipocytes, chondrocytes, and myoblasts. The differentiation of these stem cells into each of the mature functional cells may be controlled by a distinctive master gene(s) and is associated with temporal and spatial expression of diverse genes. Identification of genes that are expressed during the differentiation of the mesenchymal cells to osteoblasts is, therefore, important to obtain insights into the molecular mechanisms of osteogenesis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 21 publications
3
87
0
Order By: Relevance
“…This hypothesis is consistent with the cells of the tooth mesenchyme that also highly express periostin and undergo an EMT (Kruzynska-Frejtag et al, 2004). During cardiovascular development initially, periostin is expressed in response to signaling from the BMP and TGF-␤ family of growth factors (Horiuchi et al, 1999;Ji et al, 2000;Hall et al, 2001;Kruzynska-Frejtag et al, 2001Lindner et al, 2004). However, as development progresses, the heart must withstand the increasing influence of hemodynamic sheer stress (Stekelenburg et al, 2004).…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…This hypothesis is consistent with the cells of the tooth mesenchyme that also highly express periostin and undergo an EMT (Kruzynska-Frejtag et al, 2004). During cardiovascular development initially, periostin is expressed in response to signaling from the BMP and TGF-␤ family of growth factors (Horiuchi et al, 1999;Ji et al, 2000;Hall et al, 2001;Kruzynska-Frejtag et al, 2001Lindner et al, 2004). However, as development progresses, the heart must withstand the increasing influence of hemodynamic sheer stress (Stekelenburg et al, 2004).…”
Section: Resultssupporting
confidence: 64%
“…These mesenchymal precursors may undergo apoptosis to create and enlarge the extracellular spaces that precede delamination and/or transdifferentiate into cells that form the tendinous cords of the valvular suspensory apparatus. Since these mesenchymal cells have been shown to have the potential to form a diverse population of differentiated cells such as cardiac muscle, cartilage, bone, and bone marrow (Icardo, 1989b;Galvin et al, 2000), the expression of periostin at later stages in valvulogenesis may serve to maintain the fibrous or tendinous identity of these cells (Ji et al, 2000). We have shown that early in cardiac cushion formation, periostin is associated in fibrous strands long before the differentiated fibrous tissues could be identified within the forming valves.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, periostin interacts with structural collagens, thereby influencing mechanical properties of the ECM (Gillan et al, 2002; Kudo, 2011; Norris et al, 2007). Its expression is controlled by mechanical stimuli and growth factors, such as transforming growth factor beta, bone morphogenetic protein 2, among other signaling molecules (Aukkarasongsup, Haruyama, Matsumoto, Shiga, & Moriyama, 2013; Ji et al, 2000). …”
Section: Introductionmentioning
confidence: 99%